<---- Sponsored ads ------ >

Solve, -x2 + 6x - 5 = 0


Solution.

Given equation is -x2 + 6x - 5 = 0

Comparing it with the standard Form of Quadratic Equation ax2 + bx + c = 0

a = -1, b = 6, c = -5

As we know, discriminant = b2 - 4ac

Discriminant = (6)2 - 4(-1)(-5)

Discriminant = 36 - (20)

Discriminant = 16

Since discriminant > 0
Both roots are real and unequal.

Using quadratic formula


Roots(x1, x2) = −b ± √   b2 − 4ac 
         2a          


Roots(x1, x2) = −b ± √ D
         2a          


x1 = −b + √D
         2a          


=   −(6) + √16
         2(-1)          


=    -6 + 4
         -2          


= 1


x2 = −b - √D
         2a          


=   −(6) - √16
         2(-1)          


=    -6 - 4
         -2          


= 5


Roots: x1 = 1,     x2 = 5


Sum of roots = -b/a

Sum of roots = -(6)/(-1)

Sum of roots = 6


Product of roots = c/a

Product of roots = (-5)/(-1)

Product of roots = 5
<---- Sponsored ads ----- >

© 2020-2030 Amibba Systems Private Limited. All rights reserved.